Ways of improvement of an assessment of efficiency of activity of government bodies. (Journal of Economic Research & Business Administration, 2016)
Now many efforts for an assessment of efficiency of government bodies are applied. Reforms concerning improvement of an assessment of efficiency is one of the main issues of today. Increase of efficiency in activity of government bodies – is an indispensable condition for development of high-quality services. Now many analyses and researches in the sphere of increase of efficiency of activity of government bodies and public servants meet. In development of the theory of efficiency make a big contribution of theories of economy, management and public administration. Nevertheless, in most cases the assessment is carried out in the form of indicators and certification. Such forms of an assessment are perceived from public servants as formal, and not influencing compensation. Thus, the importance of increase of efficiency of works of government bodies, formations and developments of personnel potential of the state activity increases.
Keywords: Government body; public service; efficiency; system of an assessment; productivity of work.